Features of Microbial Landscape of Wound Surface in Patients with Diabetic Foot Syndrome - A. V. Fedoseev; R. V. Siforov; A. S. Inytin; A. A. Chekushin; D. V. Krolivec (Антибиотики и Химиотерапия, 2020)
Reliable inhibition of an infectious agent in the wound is an integral part of the therapeutic measures for the diabetic foot syndrome. Because of low immunity in patients with diabetes the use of antibiotics should be based not only on the systemic but also local signs of the infection. Unfortunately, the antibiotic therapy does not always provide adequate inhibition of the pathogens. Investigation of the microbial landscape of the wound surface and susceptibility of the pathogens to antibiotics in patients with the diabetic foot syndrome showed that the main pathogens were Staphylococcus aureus, Enterococcus faecalis, Enterobacter cloacae and the Acinetobacter baumannii complex. A detailed analysis of the microbiological tests in a particular department allows to identify the most significant pathogens, that makes it possible to assign an earlier rational empirical antibiotic therapy for such pathology.